Raumkörper : Netze und andere Gebilde. - Bideau, André; Christofori, Ralf; Pakesch, Peter; Kunsthalle Basel (Basel : Kunsthalle Basel, 2000)
Armadio, Anna ; Asawa, Ruth ; Baumann, Thomas ; Bretterbauer, Gilbert ; Crockett, Bryan ; El-Hassan, Róza ; Eliasson, Olafur ; Furter, Franziska ; Gego ; Kobalt, Owsky ; Lambie, Jim ; Larner, Liz ; Lehocká, Denisa ; Malich, Karel ; Neto, Ernesto ; Rehberger, Tobias ; Saret, Alan ; Schnitger, Lara ; Stäuble, Jürg
biog. [12 p.]
Duits
Engels
Raumkörper : Netze und andere Gebilde, Kunsthalle Basel, 26.08 - 12.11.2000
boek